ANALISIS DAN PERANCANGAN E-COMMERCE PADA GOFONE JAMBI - Oktavia, Ananda; Marthiawati, Noneng (Jurnal Informatika, Sistem Informasi dan Kehutanan (FORSINTA), 2023)
Store Gofone is a privately owned business entity that sells smartphones which are a tertiary need for people in everyday life. Initially, Gofone still sold conventional products, limited to meetings at product sales points or shops, which were deemed less effective and efficient. This is because Gofone does not yet have a dedicated e-commerce website to provide all information related to product sales. To make product sales more effective and efficient, an e-commerce website is needed. This research aims to increase market share, reduce operational costs, widen sales reach, increase consumer loyalty or loyalty to the product, as well as a promotional medium. The method used in this study is UML (Unified Modeling Language) which consists of use case diagrams, activity diagrams, and class diagrams. The design uses the prototype system method. The results of the research are in the form of an e-commerce system at Gofone Jambi.